2015
DOI: 10.1002/pip.2660
|View full text |Cite
|
Sign up to set email alerts
|

Application of copper thiocyanate for high open‐circuit voltages of CdTe solar cells

Abstract: Copper thiocyanate (CuSCN) has proven to be a low-cost, efficient hole-transporting material for the emerging organicinorganic perovskite solar cells. Herein, we report that CuSCN can also be applied to CdTe thin-film solar cells to achieve high open-circuit voltages (V OC s). By optimizing the thickness of the thermally evaporated CuSCN films, CdTe cells fabricated by close space sublimation in the superstrate configuration have achieved V OC s as high as 872 mV, which is about 20-25 mV higher than the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Figure shows the device performance for the DES‐/CuSCN‐based CdSe/CdTe solar cells with tuning the CuSCN thickness. It is reported that the sputtered CuSCN thickness can influence the CdS/CdTe devices performance remarkably, in particular, will improve the V oc , and reduce the fill factor . Without CuSCN (i.e., 0 nm, means no HTL, ERL, and Cu doping), the CdSe/CdTe device PCE is ~11%, V oc ~0.7 V, J sc ~26.5 mA cm −2 , and the Fill factor ~58%, which is similar to that of CdS/CdTe devices without CuSCN .…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…Figure shows the device performance for the DES‐/CuSCN‐based CdSe/CdTe solar cells with tuning the CuSCN thickness. It is reported that the sputtered CuSCN thickness can influence the CdS/CdTe devices performance remarkably, in particular, will improve the V oc , and reduce the fill factor . Without CuSCN (i.e., 0 nm, means no HTL, ERL, and Cu doping), the CdSe/CdTe device PCE is ~11%, V oc ~0.7 V, J sc ~26.5 mA cm −2 , and the Fill factor ~58%, which is similar to that of CdS/CdTe devices without CuSCN .…”
Section: Resultsmentioning
confidence: 59%
“…Figure B indicates the bandgap diagram calculated using SCAPS modeling . CuSCN thickness directly impacts the carrier transport due to its high resistivity and can play as a barrier for the carrier transport if the thickness is too thick . Figure C shows the two solvents in this work to tune the thickness of CuSCN layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations